PERSPEKTIF PESERTA DIDIK TENTANG KEDAMAIAN DAN RESOLUSI KONFLIK DI SEKOLAH - Akhmad, Sudaryat Nurdin; Kartadinata, Sunaryo; -, Ilfiandra (PEDAGOGIA, 2016)
Topics examined in this study are peace and conflict resolution in schools in the perspective of learners. The method used is the analysis of narratives. A total of 42 students of class XI used as study participants. Data revealed through autobiographical narratives and interviews and analyzed qualitatively. The results showed that the treatment is less educated than the teacher in the form of verbal and physical punishment as well as conflicts among students in the form of bullying and personal conflicts, an event that otherwise is not peaceful by learners. In conflict resolution with the teachers, they generally prefer to be passive and withdrawn. While the conflict with a friend, in addition, there is also no one dared passive confrontation.Learners interpret peace more likely in a positive perspective and prioritize peace with self, others, the environment and even with God. Prospects for peace ahead despite pessimistic, but generally they are convinced that with joint efforts for world peace will be achieved.Â Keywords: Peace, School , conflict resolution , cognitive style